TINJAUAN HUKUM ISLAM TERHADAP SISTEM PEMBAYARAN DIGITAL DALAM PLATFORM E-COMMERCE - Ali Achmad Muhajir; Mohammad Ridwan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The rapid development of digital transactions in e-commerce platforms has introduced various payment innovations, including e-wallets, virtual accounts, debit/credit cards, QRIS, and paylater services. This study aims to analyze the compliance of these digital payment methods with Islamic legal principles, particularly regarding contracts, fairness, public interest, and the prohibition of riba, gharar, and maisir. Using a library research approach, this study reviews literature on Islamic commercial law, regulations issued by OJK and BI, and relevant DSN-MUI fatwas. The findings indicate that most digital payment methods can be considered sharia-compliant as long as the transactional mechanisms are transparent and free from prohibited elements. However, paylater services still pose significant risks of riba due to interest charges and late payment penalties. Therefore, a stronger sharia compliance framework and integrated regulatory supervision are required to ensure that digital payment systems align with Islamic principles.